PIM Sistem Kontrol Suhu dan Gas Amonia pada Kandang Ayam berbasis Internet of Things di Mitra CV. Bintang Timur Farm - Nalendra, Adimas Ketut; Mujiono, M; Widigdyo, Anang (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
CV Bintang Timur Farm is a company in the field of chicken farming which has a partner of approximately 100 farmers. Breeders who partner with CV. Bintang Timur Farm is usually a small scale farmer. The problems that occur to farmers, especially small-scale farmers, are monitoring the temperature of the cage and managing the cleanliness of the cage. The solution that can be applied to these problems is the application of science and technology to the community of temperature and gas control systems in chicken coops based on the Internet of Things. The use of IoT technology will help farmers to be more effective and efficient in controlling the temperature and gas in the chicken coop and can be a reference for farmers to determine the right time for the cage to be cleaned. The method of implementing this activity uses the Participatory Learning and Action (PLA) method which involves partners in all of these service activities. While this service activity consists of a situation analysis FGD, making tool designs, assisting the use of tools, and evaluating program sustainability. Therefore, it is hoped that farmers can support and use IoT technology so that later they can fulfill market share. The output target resulting from this activity is to improve the skills of farmers in cultivation and management of cage hygiene by processing chicken manure into organic fertilizer, increasing chicken farm production by 5%.